Overexpression of F-Box Nictaba Promotes Defense and Anthocyanin Accumulation in Arabidopsis thaliana After Pseudomonas syringae Infection - Romero-Pérez, Andrea; Ameye, Maarten; Audenaert, Kris; Van Damme, Els J. M. (Frontiers in Plant Science, 2021)
Pseudomonas syringae pv. tomato DC3000 (Pst DC3000) is a well-known pathogen and model organism that is used to study plant-pathogen interactions and subsequent plant immune responses. Numerous studies have demonstrated the effect of Pst DC3000 on Arabidopsis plants and how type III effectors are required to promote bacterial virulence and pathogenesis. F-Box Nictaba (encoded by At2g02360) is a stress-inducible lectin that is up-regulated in Arabidopsis thaliana leaves after Pst DC3000 infection. In this study, a flood inoculation assay was optimized to check the performance of transgenic Arabidopsis seedlings with different expression levels of F-Box Nictaba after bacterial infection. Using a combination of multispectral and fluorescent imaging combined with molecular techniques, disease symptoms, transcript levels for F-Box Nictaba and disease-related genes were studied in Arabidopsis leaves infected with two virulent strains: Pst DC3000 and its mutant strain, deficient in flagellin ∆fliC. Analyses of plants infected with fluorescently labelled Pst DC3000 allowed to study the differences in bacterial colonization between plant lines. Overexpression plants showed a reduced bacterial content during the later stages of the infection. Our results show that overexpression of F-Box Nictaba resulted in reduced leaf damage after bacterial infections, whereas knock-down and knock-out lines were not more susceptible to Pseudomonas infection than wild type plants. In contrast to wild type and knock-out plants, overexpressing lines for F-Box Nictaba revealed a significant increase in anthocyanin content, better efficiency of photosystem II (Fv/Fm) and higher chlorophyll content after Pst DC3000 infection. Overexpression of F-Box Nictaba coincided with increased expression of salicylic acid (SA) related defense genes, confirming earlier data that showed that F-Box Nictaba is part of the SA-dependent defense against Pst DC3000 infection. Knock-out lines yielded no discernible effects on plant symptoms after Pseudomonas infection suggesting possible gene redundancy between F-Box Nictaba genes.